Addressing food insecurity and intersectional health-related social needs at a federally qualified health centre during the COVID-19 pandemic: a case study. Issue 2 (1st February 2023) - Styklunas, Grace M.
ABSTRACT: The COVID-19 pandemic has exacerbated preexisting health-related social needs (HRSN) in communities already facing health disparities. Federally qualified health centres (FQHC) are well positioned to understand the unique needs of diverse communities and patients. This singular case study provides a novel look into one Massachusetts FQHC's experience addressing increased hunger and poverty in their patient population. Interviews with the FQHC staff and leadership explored perspectives on the centre's current practices to address food insecurity, barriers they face, and hopes for improving community health. Interviews were recorded, transcribed, and coded using grounded theory methods. Participants were equivocal about whether food insecurity was the largest problem patients are facing. They rather emphasised the intersectional nature HRSN, including housing instability, occupational health hazards, and unemployment. Stigma associated with utilising social services, HRSN screening disruptions, and capacity limitations were barriers to addressing the community's needs. Participants highlighted the importance of patient agency; allowing patients to choose for themselves how and where they spend money to meet their health needs. The need to invest in community-centred and culturally sensitive solutions was also emphasised. Longer-term interventions, such as application assistance to federal nutrition assistance programmes, were highly favoured over emergency aid. Addressing the root causes of poverty and health disparities was recognised as essential to improving community health both during and after the pandemic. Findings highlight the importance of fostering trust and supporting community-centred and justice-oriented interventions that go beyond emergency assistance and individualised care.